Cannabinoids for the treatment of cannabis use disorder: New avenues for reaching and helping youth?. (January 2022) - Rømer Thomsen, Kristine; Thylstrup, Birgitte; Kenyon, Emily A.; Lees, Rachel; Baandrup, Lone; Feldstein Ewing, Sarah W.; Freeman, Tom P.
Highlights: Cannabis use disorder in youth is associated with adverse outcomes. THC based cannabinoid treatments reduce withdrawal, but not use, in adult samples. Non-THC based cannabinoid treatments show promising reductions in use in adults. Next step is to examine the impact of cannabinoids on youth cannabis use disorder. Abstract: Cannabis use peaks during adolescence and emerging adulthood, and cannabis use disorder (CUD) is associated with a wide range of adverse outcomes. This is particularly pertinent in youth, because the developing brain may be more vulnerable to adverse effects of frequent cannabis use. Combining evidence-based psychosocial interventions with safe and effective pharmacotherapy is a potential avenue to improve youth outcomes, but we lack approved CUD pharmacotherapies. Here, we review new potential avenues for helping youth with CUD, with a particular focus on cannabinoid-based treatments. Evidence from placebo-controlled RCTs suggests synthetic delta-9-tetrahydrocannabinol (THC) decreases withdrawal symptoms, but not cannabis use, in adults with daily cannabis use/CUD, while findings regarding formulations containing THC combined with cannabidiol (CBD) are mixed. Preliminary evidence from two placebo-controlled RCTs in adults with CUD suggests that both Fatty Acid Amide Hydrolase inhibitors and CBD can reduce cannabis use. However, larger trials are needed to strengthen the evidence. Findings from adults point to cannabinoid-based treatments as a potential strategy that should be examined in youth with CUD.